A clinically significant interaction between voriconazole and rifapentine: a case report and review of evidence - Chen, Tingting; Chen, Xiaoling; Zhang, Qingquan (Frontiers in Medicine, 2026)
We present a case of concurrent pulmonary aspergillosis and tuberculosis in a 53-year-old male, treated with voriconazole and rifapentine. In this case, co-administration with rifapentine resulted in a markedly lower voriconazole trough concentration (0.4 μg/mL on day 7) compared to that without it (4.3 μg/mL on day 25), reflecting a 90.7% reduction. After rifapentine was discontinued and the voriconazole dose was increased to 300 mg q12h intravenously (day 8), the trough concentration remained at 0.4 μg/mL two days later (day 10). Subsequently, it increased to 3.0 μg/mL by day 14 (6 days post-adjustment) and further rose to 10.8 μg/mL by day 18 (10 days post-adjustment), exceeding the therapeutic range. The results demonstrated a significant decrease in voriconazole levels during combination therapy, an effect that persisted for over one week after rifapentine was discontinued. This case illustrates that increasing the voriconazole dose immediately after rifapentine cessation is not advisable to counteract this interaction. Furthermore, therapeutic drug monitoring should be continued even after target trough levels are attained, as the waning enzyme-induction effect may subsequently lead to supra-therapeutic exposure and potential toxicity.